Régimen de insolvencia transitorio y su aplicabilidad en escenario de estabilidad : caso de las micro y pequeñas empresas en Colombia (2020)
COVID-19 was declared by the World Health Organization (WHO) as a pandemic, has allowed to identify challenges that Colombian regulation must assume in scenarios in which there are adverse economic and/or social situations. The above, to the extent that Colombian regulation, does not contemplate scenarios in which the economy may be affected by exogenous shocks that directly affect the business sector, by means of contractions in the demand and supply of goods and services, such as the one currently occurring worldwide. The economy is one of the sectors that allows measuring how developed a country is compared to others, and by connection, this derives in the confidence generated in foreign investors who evaluate making an investment in the Colombian territory. To this end, companies, as stated in Article 25 of Decree 410 of 1971, by means of which the Colombian Commercial Code is issued, any economic activity organized for the production, transformation, circulation, administration or custody of goods, or for the rendering of services must have mechanisms that allow them, in adverse scenarios, to find solutions to avoid entering into liquidation scenarios. Additionally, those measures that are useful for companies can mitigate the negative impact on factors such as employment, liquidity and solvency of a specific market. Actually, COVID-19 has had a negative impact on Colombia, as it has on most countries in the different regions of the world, thus generating great challenges for the governments of the time, in relation to the search for measures to cushion the different damages caused.